STATUS HUKUM OUTSOURCING PASCA PUTUSAN MAHKAMAH KONSTITUSI PERKARA NOMOR 27/PUU-IX/2011 - Anang Dony Irawan (Arena Hukum, 2019)
AbstractRapid response to market demands can determine victory and defeat in the competition. Therefore, these days companies are concerned with things that accelerate this process for the sake of efficiency and effectiveness of the company. One way is to handover part of the work to other parties through chartering services or providers of laborers or known as outsourcing. Legal protection of workers/laborers in the employment agreement with the outsourcing system has been regulated in articles 64 to 66 of Law No.13 of 2003 concerning labor. And for outsourcing companies it has been regulated by the Decree of the Minister of Manpower and Transmigration Kep.101/Men/VI/2004 concerning Procedures for Licensing of workers of Labour Services Providers. The establishment of the Constitutional Court of the Republic of Indonesia on August 13, 2003 gave new hope to the people of Indonesia to obtaun their constitutional rights. Th position and the relations between the state with the people in the constitutional perspective mare expected to become clearer.Â  AbstrakRespon yang cepat terhadap tuntutan pasar dapat menentukan kemenangan dan kekalahan dalam persaingan usaha. Oleh karena itu, belakangan ini perusahaan mementingkan hal-hal yang mempercepat proses ini demi efisiensi dan efektifitas perusahaan. Salah satu caranya adalah dengan menyerahkan sebagian pekerjaan kepada pihak lain melalui jasa pemborongan atau penyedia jasa pekerja/buruh atau dikenal dengan istilah outsourcing. Perlindungan hukum terhadap pekerja/buruh dalam perjanjian kerja dengan sistem outsourcing telah diatur dalam pasal 64 sampai dengan pasal 66 Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan, dan untuk perusahaan outsourcing juga telah diatur dengan Keputusan Menteri Tenaga Kerja dan Transmigrasi Nomor Kep.101/Men/VI/2004 Tahun 2004 tentang Tata Cara Perizinan Perusahaan Penyedia Jasa Pekerja/Buruh. Dibentuknya Mahkamah Konstitusi Republik Indonesia pada 13 Agustus 2003 memberi suatu harapan baru bagi rakyat Indonesia untuk mendapatkan hak-hak konstitusionalnya. Kedudukan dan hubungan antara Negara dengan rakyat dalam perspektif konstitusi diharapkan semakin jelas.Â